PENGARUH MODEL PEMBELAJARAN PROBING PROMPTING TERHADAP HASIL BELAJAR PENDIDIKAN AGAMA ISLAM - Muh Haikal Nur Fikri; Dwi Wahyudiati; Nurul Lailatul Khusniah; Abdul Manap (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT This study was motivated by the low learning outcomes in Islamic Religious Education caused by limited student engagement in the learning process. The purpose of this study was to determine the effect of the probing prompting learning model on students’ learning outcomes in Islamic Religious Education on the topic of good deeds (amal saleh) and positive thinking (husnuzan) among eighth-grade students of SMP Negeri 2 Kopang in the 2023/2024 academic year. This study employed a quantitative approach with a quasi-experimental design. The sample consisted of 86 students divided into an experimental class and a control class selected through simple random sampling. Data were collected using a multiple-choice test instrument that had met validity and reliability criteria. Data analysis was conducted using parametric statistical tests to examine differences in learning outcomes between the two groups. The results indicated that the probing prompting learning model had a significant effect on students’ learning outcomes. The implementation of this model enhanced student engagement, understanding, and participation during the learning process. Therefore, the probing prompting model can be considered an effective alternative instructional strategy to improve students’ learning outcomes in Islamic Religious Education.ABSTRAK Penelitian ini dilatarbelakangi oleh rendahnya hasil belajar Pendidikan Agama Islam yang disebabkan oleh kurangnya keterlibatan aktif siswa dalam proses pembelajaran. Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran probing prompting terhadap hasil belajar Pendidikan Agama Islam pada materi amal saleh dan husnuzan siswa kelas VIII SMP Negeri 2 Kopang tahun pelajaran 2023/2024. Penelitian ini menggunakan pendekatan kuantitatif dengan desain eksperimen semu (quasi experiment). Sampel penelitian berjumlah 86 siswa yang terdiri atas kelas eksperimen dan kelas kontrol yang dipilih secara simple random sampling. Pengumpulan data dilakukan menggunakan instrumen tes pilihan ganda yang telah memenuhi kriteria validitas dan reliabilitas. Data dianalisis menggunakan uji statistik parametrik untuk menguji perbedaan hasil belajar antara kedua kelompok. Hasil penelitian menunjukkan bahwa terdapat pengaruh signifikan penggunaan model pembelajaran probing prompting terhadap hasil belajar siswa. Penerapan model ini mampu meningkatkan keaktifan, pemahaman, dan keterlibatan siswa dalam proses pembelajaran. Dengan demikian, model probing prompting dapat menjadi alternatif strategi pembelajaran yang efektif dalam meningkatkan hasil belajar Pendidikan Agama Islam siswa.